As contribuições ao PIS e a COFINS e a aplicabilidade do princípio constitucional da não cumulatividade - Santos, José Aparecido dos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The contribution of non-cumulative PIS and COFINS was always complain taxpayers, citizens, businessmen, mainly from the clear understanding that all have the harmful effects and majoradores the tax burden arising from its cascading effect. Taxes like these are considered economically perverse, because they are actually manifestations of an impact on ability to pay previously reserved for other tax implications of institutionalizing the undesirable bis in idem. But not in its theoretical conception of double effect on one same economic data, but representing a sequence of cascading effects that overlap. Given this scenario, the claims by the prevalence and applicability of non-cumulative PIS and COFINS are increasing. To know the possibility of the application of this systematic referred to Social Contributions sought to improve them within the Brazilian tax system, which proved, according to the theory pentapartite a tax subspecies, species Special Contributions, which belongs to gender tribute side of the taxes, fees, contributions and Compulsory Loans Improvements. Once framed within the concept of tax, legal and constitutional rules must be observed. And it is in this sense that it draws a parallel between the materiality of the PIS and COFINS, with other taxes such as IPI and ICMS in order to observe the conditions of a noncumulative taxation, because until then the PIS and COFINS were being taxed cumulatively, damaging the national economy, since the incidence cascading propitiated an increased tax burden. And, in a context where the taxman stands out increasingly by their tax collection office, the search for solutions that remediam high tax burden increases every day in Brazil. In this vein, in order to eliminate the cumulative nature of these contributions, which, in theory, increase the cost and would burden the chain of production, Laws were published paragraphs. 10.637 / 02 and 10.833 / 03, changing the dynamics of...

A não cumulatividade da Contribuição ao PIS e a COFINS sempre foi reclamo dos contribuintes, cidadãos, empresários, principalmente da nítida percepção que todos têm dos efeitos prejudiciais e majoradores da carga tributária oriundos da sua incidência em cascata. Tributos como estes são tidos como economicamente perversos, pois, na verdade são incidências sobre manifestações de capacidade contributiva anteriormente reservadas a outras incidências tributárias, institucionalizando-se o indesejável bis in idem. Porém, não na sua concepção teórica de dupla incidência sobre um mesmo dado econômico, mas sim, representando uma seqüência de incidências em cascata que se sobrepõem. Diante deste cenário, os clamores pela prevalência e aplicabilidade da não cumulatividade do PIS e COFINS são cada vez maiores. Para se saber a possibilidade da aplicação desta sistemática às referidas Contribuições Sociais buscou-se aperfeiçoa-las dentro do sistema tributário brasileiro, o que se demonstrou ser, consoante a teoria pentapartite uma subespécie tributária, da espécie Contribuições Especiais, a qual pertence ao gênero tributo, ao lado dos Impostos, Taxas, Empréstimos Compulsórios e Contribuições de Melhorias. Uma vez enquadradas no conceito de tributo, regras legais e constitucionais devem ser observadas. E é neste sentido que se traçou um paralelo entre a materialidade do PIS e da COFINS, com outros tributos como o IPI e ICMS, a fim de observar as condições de uma tributação não cumulativa, pois até então o PIS e a COFINS vinham sendo tributados de forma cumulativa, prejudicando a economia nacional, pois a incidência em cascata propiciava um aumento da carga tributária. E, num contexto em que o fisco se destaca cada vez mais por sua sede arrecadatória, a busca por soluções que remediam a alta carga tributaria aumenta a cada dia no Brasil. Neste diapasão, com o propósito de..
Keywords: Direito tributário - Impostos; Contribuição social; Contribuições (Direito tributario); Tributos - Brasil; Law